2022
DOI: 10.1038/s41598-022-12408-w
|View full text |Cite
|
Sign up to set email alerts
|

Evening light environments can be designed to consolidate and increase the duration of REM-sleep

Abstract: Evening exposure to short-wavelength light has disruptive effects on circadian rhythms and sleep. These effects can be mitigated by blocking short-wavelength (blue) frequencies, which has led to the development of evening blue-depleted light environments (BDLEs). We have previously reported that residing 5 days in an evening BDLE, compared with residing in a normal indoor light environment of similar photopic lux, advances circadian rhythms and increases the duration of rapid eye movement (REM) sleep in a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…We have previously shown that the same light environment as employed in the current RCT produced changes in sleep, circadian rhythms, and arousal in healthy young adults. 17,18 Further, there were no negative effects in that population, nor in nurses’ ability to work in the blue-depleted LE at the present unit, 41 or elsewhere. 42 However, it is possible that aspects of the ‘dosage’ we employed is suboptimal.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We have previously shown that the same light environment as employed in the current RCT produced changes in sleep, circadian rhythms, and arousal in healthy young adults. 17,18 Further, there were no negative effects in that population, nor in nurses’ ability to work in the blue-depleted LE at the present unit, 41 or elsewhere. 42 However, it is possible that aspects of the ‘dosage’ we employed is suboptimal.…”
Section: Discussionmentioning
confidence: 70%
“…Our own research has shown that changing the evening light environment in an acute psychiatric unit has positive effects on the circadian, sleep and neurocognitive systems of healthy young adult volunteers. 17,18 However, it is unknown whether any change would translate into better clinical outcomes. Several mental health inpatient projects are underway, but there is limited research on the potential benefits of exposing trans-diagnostic inpatient populations to dynamic, programmable lighting conditions.…”
mentioning
confidence: 99%
“…There was no significant difference in sleep time, time to fall asleep, the proportion of deep and light sleep, proportion of REM eye movement, etc. Thus, more sophisticated equipment (such as Polysomnography (PSG)) should be used to conduct experiments with a larger sample size in subsequent studies, since low proportional blue light exposure would prolong REM sleep and advance the DLMO phase while also increasing overall sleep time [68]. While lighting in the evening can suppress melatonin secretion and delay circadian phase, the patterning of light exposure across the day and evening can have moderating effects [69].…”
Section: Discussionmentioning
confidence: 99%
“…Evening blue light restriction has proven effective in promoting circadian normalization. 70 In clinical studies, blue-blocking glasses improve subjective sleep quality, 71 reduce sleep onset latency, 72 and normalize melatonin levels. 73 To the best of our knowledge, blue-blocking glasses have not been studied as an adjuvant treatment for acute concussion.…”
Section: Circadian Therapy For Acute Concussionmentioning
confidence: 99%